Pengaruh Pengetahuan Manajer Tentang Sistem Informasi Akuntansi Manajemen Terhadap Gaya Pengendalian Manajemen - Widia Astuty (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
This study aimed 10 obtain the interpretation of the contribution of ma,wgers' knowledge influence on manogemenl accounling informMion s;ID1s lo control slyle of management. The research method using descriptive and verificative lypes. The ,mil of analysis in !his sludy is the national private commercial bank foreign exchange in orth Sumalra,and the respondents in the accounting andflnance manager. Descriplive analyzes were pe1fo1wed lo analyze /he object of research. While the verification analyzes conducted lo examine the effect of managers· knowledge about management accounting informalion SJ'Slems lo control slyle of manageG,t by Partial Least Square (PLS) 111ethods.Z11e results showed thal the bank manager is not currently use an inleraclive ma11age111en18cou111ing information, they lend lo use the diagnostic style in management acc01111ti11g information. J\1/anagers who use 111a11age111en/ accounting i1iflfltio11 with diagnostics style perceive Iha/ management accounting i1if0Bio11 is limited lo financial i1ifor111a/ion only. "t rlhermore the resulls ol hi b·1udy show Iha 111a11agers' 11owled e on accou111i11g i1ifor111alion S)'Slems 111anage111e11/